Epic time and narrativity in Jean Sibelius's Lemminkainen Suite - Portnow, Allison (2007)
Jean Sibelius’s compositions, like those of many artists in the nineteenth and early twentieth centuries, became inseparable from discourses of aesthetics and politics. The 1895 Lemminkäinen Suite (Op. 22, no. 1–4) is a work often associated with such trends: the four-movement tone poem is based on the Kalevala, a Finnish epic poem intimately tied to artistic and nationalist sentiments in Finland. Situating the Suite within the aesthetic/political movement known as Karelianism and parallel to the Kalevala as literature, I explore the musical gestures Sibelius employs that create a musical narrative reflecting its poetic source in subject, form, and mode. In analyzing the Suite’s uniquely “epic” nature, I approach the musical narrative semiologically by examining musical “topoi” within their larger formal settings. I conclude my narratological examination by focusing on musical time in the work, an element that, in encouraging a perception of expansive temporality, plays an important role in the construction of the musical epic.